Crescimento inicial de plantas de pinhão manso (Jatropa curcas L.) sob doses de fósforo e simulação de deriva de glyphosate - Matte, Sheila Cordeiro da Silva (2013)
We carried out this work with the aim of evaluating the initial growth of Jatropha (Jatropa curcas L.) under the influence of levels of phosphorus and simulated glyphosate drift. The experiment was conducted using plastic pots, packed in field conditions, we used a randomized complete block randomized in a factorial 3 x 5 (three phosphorus levels: 0, 40 and 80 kg ha-1) and five doses simulated drift of glyphosate: (0, 1.1, 3.3, 10 and 30 g ha -1), with 4 replicates. The fertilization of 40 and 80 kg ha-1 phosphorus provided the greatest increase in dry matter, height and diameter. Analyses of lignin, phosphorus also showed the highest levels of fertilization in 40 and 80 kg ha-1 phosphorus, as in photosynthesis. It was observed that the doses of 1.1 drift simulation; 3.3 g ha-1 were as highlighted taking into account the dry matter. At a dose of 30 g ha-1 plant tends to be susceptible to glyphosate drift, reducing the plant dry matter. Phosphorus fertilization, tends to make plants more tolerant jatropha glyphosate drift